The Effect of Complete Dentures on The Body Mass Index of Elderly Patients - Andi Alifianti Puteri Asegaff; Nova Adrian (Indonesian Dental Association, 2019)
Introduction: As people age, physical changes, such as complete tooth loss, can occur. The therapy for complete tooth loss is to wear complete dentures (CDs). However, this can affect patients’ body mass index (BMI) and overall health, especially in patients who are elderly. BMI is an indicator that is often used to determine a person’s nutritional status. Objective: The aim of this study was to analyze the effect of wearing a new set of full upper and lower dentures affects the BMI of elderly patients, one month after insertion at Dental Hospital of Dentistry Faculty, Trisakti University. Method: This was an observational analytic study with a cross-sectional design. The subjects of this study were 31 elderly patients (according to the World Health Organization [WHO] age classification). Result: Of the 31 elderly patients studied, 7 had an unstable or fluctuating BMI, 12 had a stable BMI from the beginning of CD insertion, 4 showed a consistent increase in BMI, and 2 showed a consistent decrease in BMI but remained in the normal BMI range. Using Spearman’s rank correlation coefficient, the result was shown to be significant (p=0.00), which means there was a strong correlation between CD use and change in BMI (0.76–0.99). Conclusion: It can be concluded that elderly patients at Dental Hospital of Dentistry Faculty, Trisakti University who are wearing CDs encounter a significant change in BMI. Most of the subjects reached a normal BMI by one month after CD insertion, caused by an increased ability to masticate effectively.